KONSEP PEMBAHARUAN PENDIDIKAN AGAMA ISLAM MENURUT NAHDATUL ULAMA - Rizal, Afri Eki; Iswantir, Iswantir (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to examine in a simple way the concept of education under the auspices of Nu, from its inception until now. In its history, the existence of the NU organization cannot be separated from the history of archipelago education in this country. There is a special vision and mission that is carried out by NU in the establishment of its organization and various institutions under its auspices. This vision is the teachings of Aswaja and its mission is to empower people. The embodiment of this vision and mission is carried out through educational media, da'wah and various other self-actualizations by means of available institutions. The concept of NU education is inseparable from the development of da'wah and the process of Islamic boarding schools on the island of Java, in this case KH. Hasyim Asy'ari as the founder of the organization along with other clerics took part in NU education. The NU organization, which is the largest organization in Indonesia, was originally categorized as traditionalist, and the initial concept of education was carried out by KH.